A Flow Cytometry-Based Assay for the Measurement of Total Complement Activity in the Serum and Clinical Practice. (10th January 2022) - Ding, Xuewei; Li, Shijun; Liu, Hui
Abstract : Objective . To develop a novel sensitive and accurate assay suitable for high-volume testing of the total complement activity in the serum for clinical laboratories. Methods . The total complement activity (TCA) to be measured was quantified by detecting the number of fragments produced by erythrocyte lysis and the erythrocyte fragmentation index (EFI), indicating TCA. EFI = M × M 2 / M 1 + M 2, where M is the number of erythrocyte fragments (removed from the background), M 1 is the number of unagglutinated red cells, M 2 is the number of agglutinated red cell groups, and M 2 / M 1 + M 2 is the agglutination coefficient indicating the degree of erythrocyte agglutination. Mild changes in hemolysin and erythrocyte concentrations were made to optimize the testing conditions. The same serum samples were tested for 10 consecutive days to determine the stability of the experimental results. Serum EFI was detected in both nephrotic syndrome patients and healthy subjects. Results . There was a linear relationship between hemolysin and erythrocyte agglutination (r = 0.999, P < 0.001 ). A good linear relationship existed between EFI and TCA (r = 0.991, P < 0.001 ). The results were not affected by slight fluctuations in the concentrations of hemolysin or erythrocytes. The interbatch CV = 8.6 % of the test results showed good stability. There was a significant difference in the EFI between nephrotic syndrome patients and healthy individuals, P < 0.001, and EFI was reduced in nephrotic syndrome patients compared to healthy individuals. Conclusion . The flow cytometry-based assay for TCA was sensitive and accurate and had potential value for clinical application.